Visual cues enhance user performance in virtual environments - Hwang, Yongsuk; Shin, Donghee (Social behavior and personality, 2018)
We examined the effects of visual cueing in an effort to identify the optimal way to present information in a 3-dimensional (3D) virtual environment. To strategically compensate for the lack of permanency, we combined dynamic and static visualizations into 1 medium by adding transparent static images (visual cueing) to an animation. A between-subjects experiment (N = 100) was conducted to examine the effects of visual cueing on cognitive load and learning outcomes. Results showed that combining dynamic and static visualizations was beneficial for reducing cognitive load, although it did not improve learning outcomes. On the basis of our findings, we suggest a design strategy for improving the effectiveness of 3D instructional animations that is broadly applicable to numerous learning contexts, such as virtual or augmented reality.